2012
DOI: 10.15193/zntj/2012/80/072-080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milk Production Season on Profile of Fatty Acids in Milk Fat

Abstract: Badano wpływ sezonu produkcji mleka na zawartość kwasów tłuszczowych w tłuszczu mlekowym. Materiałem badanym był tłuszcz mlekowy pozyskany metodą ekstrakcyjną z niepasteryzowanej 30 % śmietanki. Próbki do badań pobierano 12 razy w miesiącu przez cały rok. Profil kwasów tłuszczowych w tłuszczu mleka określano metodą chromatografii gazowej. Przeprowadzone badania wskazują, że sezon produkcji mleka wywiera istotny wpływ na profil kwasów tłuszczowych tłuszczu mlekowego oraz proporcje kwasów tłuszczowych nienasycon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The quantitative composition of fatty acids in milk fat changes under the influence of various factors, such as: animal feeding, breed, lactation stage, individual characteristics, climatic conditions, health, age, and others [ 26 , 27 , 28 , 29 , 30 ]. Of the factors mentioned, animal feeding has the greatest influence, which includes pasture feeding, consumption of grass, hay, or silage [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Fat from milk obtained in the green feed season contains much more C18 acids, mainly C18:1 acid, and much less palmitic and myristic acid than the one obtained in the cowshed feeding season [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative composition of fatty acids in milk fat changes under the influence of various factors, such as: animal feeding, breed, lactation stage, individual characteristics, climatic conditions, health, age, and others [ 26 , 27 , 28 , 29 , 30 ]. Of the factors mentioned, animal feeding has the greatest influence, which includes pasture feeding, consumption of grass, hay, or silage [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Fat from milk obtained in the green feed season contains much more C18 acids, mainly C18:1 acid, and much less palmitic and myristic acid than the one obtained in the cowshed feeding season [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fat from milk obtained in the green feed season contains much more C18 acids, mainly C18:1 acid, and much less palmitic and myristic acid than the one obtained in the cowshed feeding season [ 39 , 40 ]. Milk fat from the pasture period of cow’s feeding is also characterized by a higher content of cis 9 trans 11 C18:2 conjugated linoleic acid and C18:1 and C18:2 trans isomers [ 30 , 34 , 38 ]. A study conducted by Żegarska et al [ 38 ] indicated that the proportion of cis 9 trans 11 C18:2 acid in fat from the winter period ranged between 0.32% to 0.52% of the total fatty acids composition, whereas in fat from the summer period, it was from 1.06% to 1.76%.…”
Section: Introductionmentioning
confidence: 99%